Impact of preoperative psychological support on outcomes in pancreatic cancer surgery: a propensity score-matched cohort study - Min, Li; Jiang, Suyan; Lu, Yanli; Zhang, Xinyu (Frontiers in Oncology, 2025)
BackgroundPreoperative multidisciplinary psychological support (PMPS) has been associated with improved outcomes in several cancer populations, but its impact in pancreatic cancer remains underexplored.MethodWe retrospectively reviewed 347 patients who underwent surgical treatment for pancreatic cancer between January 2020 and December 2022. Among them, 132 patients received preoperative multidisciplinary psychological support (PMPS), while 215 did not. To reduce confounding, 1:1 propensity score matching (PSM) was performed based on age, sex, comorbidities, tumor stage, and type of surgery, yielding 132 matched pairs (n = 264). The PMPS intervention included structured psychological counseling, perioperative education, relaxation techniques, and coordinated physical therapy. Primary outcomes were postoperative complication rate, length of hospital stay, and in-hospital mortality. Secondary outcomes included 30-day readmission, psychological status assessed by the Hospital Anxiety and Depression Scale (HADS), and patient satisfaction. Logistic regression and ROC analysis were conducted to evaluate the impact of PMPS.ResultsCompared with the control group, patients in the PMPS group had a significantly lower incidence of postoperative complications (17.4% vs. 30.3%, P = 0.011), shorter hospital stay (10.0 ± 2.7 vs. 12.8 ± 3.3 days, P<0.001), and reduced in-hospital mortality (2.3% vs. 5.3%, P = 0.048). PMPS was associated with significantly improved postoperative anxiety and depression scores (P<0.001). Logistic regression indicated that PMPS independently reduced the risk of major complications (OR = 0.51, 95% CI: 0.30–0.88, P = 0.015). ROC curves demonstrated predictive value of PMPS for readmission (AUC = 0.725) and postoperative anxiety (AUC = 0.833).ConclusionPMPS was associated with improved perioperative and psychological outcomes in patients undergoing pancreatic cancer surgery. Although this was a retrospective single-center study, our findings suggest that structured psychological support may have clinical value and should be considered as part of routine multidisciplinary care. Future multicenter prospective studies are warranted to validate these results.